Chitosan–plasmid DNA nanoparticles encoding small hairpin RNA targeting MMP‐3 and ‐13 to inhibit the expression of dedifferentiation related genes in expanded chondrocytes. Issue 2 (14th May 2013) - Zhao, Jingxin; Fan, Xiangli; Zhang, Qiang; Sun, Fangfei; Li, Xiaojian; Xiong, Chuan; Zhang, Chunli; Fan, Hongbin
Abstract Overexpression of matrix metalloproteinase (MMP)‐3 and ‐13 can lead to the dedifferentiation of expanded chondrocytes. After implanting dedifferentiated cells for cartilage defect repair, graft failure may occur. Short hairpin RNA (shRNA) is a powerful genetic tool to reduce the expression of target genes. This study investigated the effects of chitosan–plasmid DNA (pDNA) nanoparticles encoding shRNA targeting MMP‐3 and ‐13 on the dedifferentiation of expanded chondrocytes. The objective was to optimize the parameters of chitosan–pDNA formulation for achieving higher efficiency of pDNA delivery and gene silencing. The chitosan–pDNA nanoparticles were prepared using a complex coacervation process. Then the characteristics including size, shape, stability, and transfection efficiency were compared in different groups. The results indicated that chitosan of 800 kDa at N/P ratio of 4 and pH 7.0 was optimal to prepare chitosan–pDNA nanoparticles. These nanoparticles showed high DNA loading efficiency (95.8 ± 1.5%) and high gene transfection efficiency (24.5 ± 1.6%). After the expanded chondrocytes were transfected by chitosan–pDNA nanoparticles, MMP‐3‐610 and MMP‐13‐2024 groups showed greater suppression in mRNA and protein levels. The results indicated that chitosan–pDNA nanoparticles encoding shRNA targeting MMP‐3 and ‐13 had great potential in silencing the dedifferentiation‐related genes for regenerating prolonged and endurable cartilage. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 373–380, 2014.